PENERAPAN FUNGSI MANAJERIAL KEPALA SMA NEGERI DALAM MANAJEMEN BERBASIS SEKOLAH - Rohmanianti, Rohmanianti (Eklektika: Jurnal Pemikiran dan Penelitian Administrasi Pendidikan, 2014)
The Implementation of Managerial Funcotion of Principal of SMAN 2 in School based Managemen in Polewali Mandar. This is a qualitative research with a case study approach on the level of school organization. Data sources of this research were set purposively by conducting interview, documenatation and observation and justified trough triangulation and member check. The result reveal that: (i) the implementation of managerial function of principal at SMAN 2 Polewali on the planning aspect is in accordance with the planning function, (ii) the implementation of managerial function of principal at SMAN 2 Polewali on the organization aspect is in accordance with the organizational function, (iii) the implementation of managerial function of principal at SMAN 2 Polewali on the motivation aspect still need to be improved, (iv) the implementation of managerial function of principal at SMAN 2 Polewali on the controlling aspect still need to be improved, (v) managerial autonomy of principal at SMAN 2 Polewali in MBS still need to improved in the from innovation policy, (vi) managerial transparency of principal at SMAN 2 Polewali in MBS is accordance with the transparency function, (vii) managerial accountability of principal at SMAN 2 Polewali in MBS is horisonatally in accordance with the transparency function, but vertically it still need improvement,(viii) community participation on the implementation of managerial function of principal at SMAN 2 Polewali in MBS yet maximal, (ix) the implementation of managerial function of participal at SMAN 2 Polewali still need to be improved.